Mode Switch of Ca2 + Oscillation-Mediated Uterine Peristalsis and Associated Embryo Implantation Impairments in Mouse Adenomyosis - Qu, Mingzi; Lu, Ping; Bellve, Karl; Lifshitz, Lawrence M.; ZhuGe, Ronghua (Frontiers in Physiology, 2021)
Adenomyosis is a debilitating gynecological disease of the uterus with no medicinal cure. The tissue injury and repair hypothesis for adenomyosis suggests that uterine hyperperistalsis or dysperistalsis plays a pivotal role in establishing adenomyotic lesions. However, specific impairments in uterine peristalsis and the underlying cellular signals for these changes in adenomyosis remain elusive. Here, we report a precision-cut uterine slice preparation that preserves in vivo uterine architecture and generates peristalsis similar to that seen in the whole uterus. We found that uterine peristalsis in neonatal mice at day 14 and adult mice at day 55 presents as bursts with multiple peaks induced by intracellular Ca2+ oscillations. Using a mouse model of adenomyosis induced by tamoxifen, a selective estrogen receptor modulator, we discovered that uterine peristalsis and Ca2+ oscillations from adenomyotic uteri on days 14 and 55 become spikes (single peaks) with smaller amplitudes. The peak frequency of Ca2+ oscillations or peristalsis does not show a difference between control and adenomyotic mice. However, both the estimated force generated by uterine peristalsis and the total Ca2+ raised by Ca2+ oscillations are smaller in uteri from adenomyotic mice. Uteri from adenomyotic mice on day 14, but not on day 55, exhibit hyperresponsiveness to oxytocin. Embryo implantations are decreased in adenomyotic adult mice. Our results reveal a mode switch from bursts to spikes (rather than an increased peak frequency) of uterine Ca2+ oscillations and peristalsis and concurrent hyperresponsiveness to oxytocin in the neonatal stage are two characteristics of adenomyosis. These characteristics may contribute to embryo implantation impairments and decreased fertility in adenomyosis.